Sympatho-adrenal hyperactivity—the key to irreversible shock?. Issue 526 (August 1969) - Irving, M. H.
Abstract : There would appear sound evidence on which to incriminate sustained sympatho-adrenal hyperactivity as a deleterious factor of prime importance in hypovolaemic shock. The use of sympathomimetics in the treatment of shock of this type is irrational and deleterious. Their rational use in those few cases of clinical shock where they are indicated will have to await knowledge of plasma catecholamine levels in such cases. Experimental studies involving α- and β-adrenergic blockade, unilaterally and in combination, have revealed that, contrary to previous theories, deterioration is mediated through both receptor types. Many of the current concepts of the pathophysiology of shock will need reassessment in the light of as yet unappreciated facets of catecholamine activity.